Exploring friendship quality and the practice of savoring in relation to the wellbeing of Greek adults - Pezirkianidis, Christos; Christopoulou, Maria; Galanaki, Evangelia; Kounenou, Kalliope; Karakasidou, Eirini; Lekka, Dimitra; Kalamatianos, Antonios; Stalikas, Anastassios (Frontiers in Psychology, 2023)
Previous research findings demonstrate that both savoring ability and the presence of high-quality friendships play a significant role in enhancing one's overall sense of wellbeing. However, these associations have not been thoroughly investigated within a diverse range of adults across their lifespans, nor have they been explored in the specific cultural context of Greece. Thus, the primary objective of this study was to delve into the relationships between close friendship quality, the utilization of savoring techniques, and wellbeing within the Greek cultural framework. The study involved 771 adults from Greece with an average age of 38.35 years, who completed the McGill Friendship Functions Questionnaire, the PERMA Profiler, and the Abridged Ways of Savoring Checklist. Results revealed that there exists a positive correlation between friendship quality and savoring strategies with overall wellbeing.Moreover, the study identified a significant association wherein a greater employment of savoring strategies was linked to higher levels of friendship quality. While this study contributes valuable insights, it also has limitations that warrant acknowledgment. Furthermore, suggestions for potential future research directions are proposed, and the implications of these findings are discussed in relation to interventions aimed at enhancing both friendships and the practice of savoring across various contexts.